Spain - Lusted, Marcia Amidon (Minneapolis : ABDO Pub. Co., 2013)
Explore diverse landscapes, travel back in time, and discover unique populations, all without leaving your chair! Start your international tour in Spain, land of the Alhambra Palace, flamenco music, the Pyrenees Mountains, and so much more. This colorful, informative book introduces Spain's history, geography, culture, climate, government, economy, and other significant features. Sidebars, maps, fact pages, a glossary, a timeline, historic images and full-color photos, and well-placed graphs and charts enhance this engaging title.
1180L
Keywords: Spain